Homeobox A1 Facilitates Immune Escape and Alleviates Oxidative Stress in Lung Adenocarcinoma. (19th May 2022) - Zhao, Fen; Tian, Hui; Liu, Xinchao; Guan, Yuanxiazi; Zhu, Ying; Ren, Peng; Zhang, Jianbo; Dong, Yinjun; Fu, Lei
Abstract : Objective . Recent studies have demonstrated that homeobox A1 (HOXA1) is upregulated in lung cancer due to RNA modifications (N 6 -methyladenosine), but the specific function of HOXA1 in lung adenocarcinoma (LUAD) remains indistinct. Herein, we investigated the role of HOXA1 in LUAD biology. Methods . This study presented pancancer analysis of associations of HOXA1 with prognosis, TMB, and immune checkpoints. The expression of HOXA1 was detected in LUAD and normal tissues with immunohistochemistry and western blot. Through least absolute shrinkage and selection operator (LASSO) analysis, HOXA1-derived gene model was conducted in LUAD. Correlations of HOXA1 with immune cell infiltrations, immune checkpoints, HLAs, and chemotherapeutic sensitivity were evaluated. Colony formation, proliferation, and migration of LUAD cells with si-HOXA1 transfection were investigated, and the effects of HOXA1 on T cell exhaustion were assessed in vitro . Results . HOXA1 expression was a risk factor of overall survival, disease-specific survival, and progression-free interval of LUAD. HOXA1 exhibited prominent associations with immune cell infiltration, immune checkpoints, and HLAs. HOXA1-derived gene signature reliably and independently predicted LUAD outcomes. Also, high-risk cases presented increased sensitivity to cisplatin, paclitaxel, docetaxel, vinorelbine, and etoposide. HOXA1 knockdown exhibited an inhibitory effect on proliferation and migration abilities of LUAD cells. Silencing HOXA1 weakened the expression of antioxidative stress markers Nrf2/HO-1 and T cell exhaustion marker CD155 in LUAD cells. Moreover, LUAD cells with HOXA1 knockdown enhanced the CD8+ T cell response. Conclusion . Our data support the oncogenic function and prognostic significance of HOXA1 that facilitates immune escape and alleviates oxidative stress of LUAD.